Global banking standards and low income countries: Helping or hindering effective regulation? - Emily Jones (University of Oxford, Global Economic Governance Programme (GEG), 2014)
Should Low Income Countries (LICs) adopt new global banking standards? The global financial crisis stimulated a series of reform initiatives to strengthen financial regulation, including a new set of global banking standards (Basel III), which all countries are being encouraged to adopt. This paper scrutinises a relatively thin body of scholarly and policy research to establish what we know about LICs and global banking standards and propose a future research agenda. Two findings stand out from this analysis. First, there is a high level of concern in the scholarly and policy literature about the appropriateness of Basel standards, particularly Basel II and III, for countries with nascent financial sectors. Second, despite these concerns and minimal participation in relevant decision-making processes, many LICs are going ahead to implement the latest standards. Strikingly, available data suggests that low-income and lower-middle income countries are just as likely to implement Basel standards as high and upper-middle countries. There is a pressing need for more in-depth research on the economics and political economy of global banking standards and LICs and I propose an agenda for future research.
Keywords: 330; Bankenregulierung; Standardisierung; Basler Akkord; Entwicklungsländer